What matters most in Cirebon, Indonesia: cultural nuances to health-related stigma - Yoslien Sopamena; Raden Sutiawan; Marlies J. Visser; Dadun Dadun; Rita Damayanti; Dien Anshari; Lawrence Yang; Ruth M. H. Peters; Marjolein B. M. Zweekhorst (Global Public Health)
Individuals with stigmatised health conditions face adverse attitudes, social exclusion and discrimination, stemming from preconceived notions about the condition and its associated symptoms or links to disability. Culture plays a role in shaping stigma manifestations. By employing the ‘what matters most’ framework, this study sought to capture perspectives of men and women living with leprosy, lymphatic filariasis or depressive disorder, and of their families and healthcare providers, regarding key cultural capabilities that ‘matter most’ for men and women in Cirebon Regency, Indonesia. A total of 91 respondents participated in 45 interviews and 10 focus group discussions. Data were analysed using thematic content analysis and the analysis generated three core cultural themes defined as ‘what matters most’ in Cirebon Regency: personal responsibilities, marriage and family responsibilities, and community responsibilities. Specifically, recovery-oriented attitudes, family support and community engagement were identified as key cultural engagements that could help people with stigmatised conditions to maintain personhood and mitigate health-related stigma. In conclusion, our findings highlight it is important to consider these cultural capabilities in stigma research, particularly in the design of stigma assessment and stigma-reduction interventions.